Black hole obscuration and duty-cycles mediated by AGN feedback in high-redshift galaxies. Issue 1 (14th May 2019) - Trebitsch, Maxime; Volonteri, Marta; Dubois, Yohan
Abstract: Dense gas in the centre of galaxies feeds massive black holes, but can also become a source of obscuration and limit our ability to find faint active galactic nuclei (AGN). We use a high-resolution cosmological radiative hydrodynamics simulation to connect the properties of the gas in the central region (a few tens of parsec) of a high-redshift galaxy to the growth of a massive black hole during the first billion years of the Universe. We find that the feedback from the AGN efficiently controls the growth of the black hole and limits the duration of the high accretion episodes by emptying the gas reservoir. As the galaxy grows in mass, the production of metals results in the presence of dust-enriched gas in the galaxy centre that can obscure highly accreting black holes enough to strongly reduce their UV/optical visibility. We also find that the gas outside the very centre of the galaxy can contribute to the total column density and obscuration at a level at least comparable to the gas in the nuclear region. We suggest that this explains the different duty-cycles required to explain the masses of high-redshift quasars and the observed UV/optical luminosity functions: in our case, the AGN would be observed with an X-ray luminosity above L_X = 10^42 erg s^-1 around 30 per cent of the time, but with UV magnitude brighter than M 1450 = −23 only 4 per cent of the time.